2020
DOI: 10.1016/j.jcv.2020.104473
|View full text |Cite
|
Sign up to set email alerts
|

Alltest rapid lateral flow immunoassays is reliable in diagnosing SARS-CoV-2 infection from 14 days after symptom onset: A prospective single-center study

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 23 publications
2
38
2
Order By: Relevance
“…Nevertheless, as RDTs are meant to be used without centrifugation, the implication of this observation is merely technical. Our results contrast with current RDT data available in the literature [ 2 , 3 , 4 , 5 , 15 , 16 ]. Indeed, Cassaniti and colleagues tested a RDT in the specific setting of acute diagnosis in the emergency department and found very low performance, thus suggesting that RDTs should be avoided in this particular acute clinical setting with potentially very short DPDs.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, as RDTs are meant to be used without centrifugation, the implication of this observation is merely technical. Our results contrast with current RDT data available in the literature [ 2 , 3 , 4 , 5 , 15 , 16 ]. Indeed, Cassaniti and colleagues tested a RDT in the specific setting of acute diagnosis in the emergency department and found very low performance, thus suggesting that RDTs should be avoided in this particular acute clinical setting with potentially very short DPDs.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent reviews have shown that nucleic acid-based methods are prone to false negative results because of insufficient viral RNA at the point of detection [ 4 ], and that antibody-based methods have slightly lower sensitivity but higher accuracy compared to molecular assays [ 5 ]. Serological assays have been suggested for the diagnosis of the infection [ 6 ] and combining the two methods is recommended to improve the detection accuracy of COVID-19 [ [4] , [5] ]. Although accurate, laboratory-based assays cannot guarantee the massive case finding so helping curb the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…As other virus affecting the respiratory traits, also SARS CoV-2 elicits the production of another class of specific immunoglobulins A (IgA) in respiratory specimens and the presence of specific anti-SARS CoV-2 IgA in the blood has also been reported [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. Hence, we conceived a novel diagnostic strategy that aimed at targeting the ‘total antibody’ response elicited by SARS CoV-2 infection to enhance sensitivity and, hopefully, expedite diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rapid lateral flow assays for IgG and IgM antibodies produced during the COVID-19 epidemic have been developed [ 11 ]. Several reports have shown that COVID-19 IgG/IgM lateral flow immunoassays may be a reliable tool to diagnose SARS-CoV-2 infection from 14 days of onset of symptoms [ 12 , 13 ]. In some countries, rapid diagnostic testing for COVID-19 has been incorporated into the local guidelines for testing asymptomatic contacts of positive cases, at day 14 of home surveillance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%